Needs Analysis on English Learning Materials for International Class Program (ICP) of Biology at Universitas Negeri Makassar - Halim, Abd; Dollah, Syarifuddin; Alam, A. Nur (JOLLT Journal of Languages and Language Teaching, 2024)
When it comes to efficiently developing and implementing a language program, doing a needs analysis is necessary. Thus, to fulfill students' English language demands in the International Class Program (ICP) of the Biology Department at Universitas Negeri Makassar, it is important to ascertain the learning requirements of students. This study aimed to find out students’ expectations about English learning materials, and to assess their efforts to achieve it. This study employed a mixed-method approach to assess the needs of the students, integrating both qualitative and quantitative research approaches. The research included a total of 34 participants, comprising 31 second-year students enrolled in ICP of the Biology Department, 1 English lecturer, and 2 alums of the same program. The questionnaire and the interview were the instruments used to gather information. The study's results showed that students need English learning materials that are related to what they are studying. To improve their English, it was very important for the students to have access to the right English materials. Researchers looked at the learning needs of the students and found that they all had different levels of English ability. The students thought that reading and speaking were the most important skills to learn in order to be fluent in English. The most common problem the students had was incorrect grammar use. The students who took part in the ICP had different ways of learning, as shown by the analysis of goal needs. Some of these ways were reading English-language books and watching videos or movies. The most important ones were to improve their self-esteem and get ready for future job prospects. Reading English-language books, watching movies, and listening to music were the main things that students did to improve their English language skills.